Exploiting hydrogen bonding interactions to probe smaller linear and cyclic diamines binding to G-quadruplexes: a DFT and molecular dynamics study. Issue 18 (20th April 2017) - Kanti Si, Mrinal; Sen, Anik; Ganguly, Bishwajit
Abstract : This report reveals that hydrogen bonding interactions between the ligand and G-quadruplex can initiate an alternative binding motif to typical π-stacking interactions. Abstract : G-quadruplexes are formed by the association of four guanine bases through Hoogsteen hydrogen bonding in guanine-rich sequences of DNA and exist in the telomere as well as in promoter regions of certain oncogenes. The sequences of G-quadruplex-DNA are targets for the design of molecules that can bind and can be developed as anti-cancer drugs. The linear and cyclic protonated diamines have been explored to bind to G-quadruplex-DNA through hydrogen bonding interactions. The quadruplex-DNA binders exploit π-stacking and hydrogen bonding interactions with the phosphate backbone of loops and grooves. In this study, linear and cyclic protonated diamines showed remarkable binding affinity for G-tetrads using hydrogen bonding interactions. The DFT M06-2X/6-31G(d)//B3LYP/6-31+G(d) level of theory showed that the cyclic ee-1, 2-CHDA (equatorial–equatorial form of 1, 2-disubstituted cyclohexadiamine di-cation) binds to the G-tetrads very strongly (∼70.0 kcal mol −1 ), with a much higher binding energy than the linear protonated diamines. The binding affinity of ligands for G-tetrads with counterions has also been examined. The binding preference of these small ligands for G-tetrads is higher than for DNA-duplex. The binding affinity of an intercalated acridine-based ligand (BRACO-19) for G-quadruplexes has been examined and the binding energy is relatively lower than that for the 1, 2 disubstituted cyclohexadiamine di-cation with G-tetrads. The atoms-in-molecules (AIM) analysis reveals that the hydrogen bonding interactions between the organic systems with G-tetrads are primarily electrostatic in nature. The molecular dynamics simulations performed using a classical force field (GROMACS) also supported the phosphate backbone sites of G-quadruplex-DNA to bind to these diamines. To mimic the structural pattern of BRACO-19, the designed inhibitor N, 2-bis-2(3, 4-aminocyclohexyl) acetamide (9 ) examined possesses two 1, 2-CHDA moieties linked through an acetamide group. The molecular dynamics results showed that the designed molecule9 can efficiently bind to the base-pairs and the phosphate backbone of G quadruplex-DNA using H-bonding interactions. The binding affinity calculated for the intercalated acridine-based drug (BRACO-19) with G-quadruplexes is weaker compared to ee-1, 2-CHDA. These ligands deliver a different binding motif (hydrogen bonding) compared to the reported G-quadruplex binders of π-delocalized systems and will kindle interest in examining such scaffolds to stabilize DNA.